2002
DOI: 10.4049/jimmunol.168.6.2930
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Influenza Virus Infection in Polymeric Ig Receptor Knockout Mice Immunized Intranasally with Adjuvant-Combined Vaccines

Abstract: The role of secretory IgA in conferring cross-protective immunity was examined in polymeric (p)IgR knockout (KO) mice immunized intranasally with different inactivated vaccines prepared from A/PR/8/34 (H1N1), A/Yamagata/120/86 (H1N1), A/Beijing/262/95 (H1N1), and B/Ibaraki/2/85 viruses and infected with the A/PR/8/34 virus in the upper respiratory tract (RT)-restricting volume. In wild-type mice, immunization with A/PR/8/34 or its variant (A/Yamagata/120/86 and A/Beijing/262/95) vaccines conferred complete pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 193 publications
(146 citation statements)
references
References 58 publications
(47 reference statements)
7
137
2
Order By: Relevance
“…In contrast, S-IgA has been shown to be more cross-reactive with drifted strains [52] and an ideal influenza vaccine would also benefit from the induction of S-IgA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, S-IgA has been shown to be more cross-reactive with drifted strains [52] and an ideal influenza vaccine would also benefit from the induction of S-IgA.…”
Section: Discussionmentioning
confidence: 99%
“…Densitometric measurements of protein bands were analyzed and quantified with the NIH Image J software. The anti-SC antibody used in this Western blot detected 2 bands at ∼120 kDa and ∼94 kDa representing pIgR and secretory component (SC), respectively [2,27]. The combined value of these two bands was determined for the quantitation of the pIgR protein expression in each case [1].…”
Section: Western Blot For Pigr Expressionmentioning
confidence: 99%
“…1B). Previous studies have shown that secretory IgA (SIgA) may play an important role in protecting against variant influenza virus infections in the upper respiratory tract (9). Thus, we used pIgR Ϫ/Ϫ mice in which the transepithelial transport of dimeric IgA is blocked to measure whether IgA Abs in the mucosal compartments induced by s.l.…”
Section: Sublingual Administration Of Inactivated A/pr/8 Virus Inducementioning
confidence: 99%